2015
DOI: 10.1002/pmj.21498
|View full text |Cite
|
Sign up to set email alerts
|

Toward High Reliability Project Organizing in Safety-Critical Projects

Abstract: ■High reliability organizations claim to be special organizations that have consistently demonstrated safe performance in operating environments, which are simultaneously of high technical complexity, high consequence, and high tempo. This article argues that the literature on high reliability organizing, which emerged through studying dayto-day operations in the nuclear industry, air traffic control industry, and U.S. navy aircraft carriers, might hold important lessons for how the project management communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…After excluding duplicate studies, the titles and abstracts were screened for 2724 records, and after all inclusion and exclusion criteria were applied 15 studies were included in the qualitative synthesis using the CASP tool ( Table 2). Of the 15 studies, seven studies [23,[36][37][38][39][40][41] were identified through hand searching of the reference lists of all studies [23,27,30,[36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding duplicate studies, the titles and abstracts were screened for 2724 records, and after all inclusion and exclusion criteria were applied 15 studies were included in the qualitative synthesis using the CASP tool ( Table 2). Of the 15 studies, seven studies [23,[36][37][38][39][40][41] were identified through hand searching of the reference lists of all studies [23,27,30,[36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…They also found out that the strategies used to prevent production errors minimised the likelihood of accidents, restricting work interruptions and control of production pressures; using skilled personnel for specific task played a vital role in managing safety and productivity [38]. Saunders [40], in her study on safety critical projects, observed that they are similarities between safety critical projects and HROs, and lessons can be learnt to improve the management of safety critical projects [40]. Management plays a key role in safety management; therefore, for project management practitioners to succeed, they need to be trained to maintain an attitude of mindfulness and conscious deliberation, and be flexible while maintaining focus on project goals [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations